Developing social skills in managers : advances in group training - Cooper, Cary L. (New York : The Macmillan press Ltd, 1976)
The book consists of three articles which provide an introduction to experiential learning groups. In the first there is a description of an organizational T-group, which is provided to highlight some of the characteristics common to most experiential groups. The second article describes the development and evolution of group methods, reflecting the main developments in the past two decades. In the third article, a taxonomy of recent group experiences is provided, highlighting the magnitude of developments within the human potential movement.
"A Halsted Press book."
Includes bibliographical references and index.
hza 20/07/2018
Loans
Keywords: Executives; Group relations training; Social skills